2021
DOI: 10.1155/2021/6661346
|View full text |Cite
|
Sign up to set email alerts
|

Greater and More Focused Measures Are Needed to Tackle Diabetes and Obesity Epidemics in the Nations of the Gulf Cooperation Council

Abstract: Beyond the suffering of the affected subjects, type 2 diabetes (T2D) and obesity epidemics gripping the Gulf Cooperation Council (GCC) states are expected to seriously jeopardize these nations’ economies and development due to productivity losses. Available data show that healthcare budgets in GCC nations are under tremendous pressure because of diabetes- and obesity-linked comorbidities. Furthermore, T2D, once an over-forties disease, risks becoming a whole-adult-life condition because of obesity-associated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…[20][21][22][23] The DISCOVER program illustrated a substantial burden of microvascular complications (including CKD and albuminuria) and macrovascular complications (primarily coronary artery disease, HF, and stroke). 24 Another multinational study (CAPTURE) showed that people with T2DM and established CVD (33%) have a higher burden of renal dysfunction (microalbuminuria [31.8% vs 20.6%], macroalbuminuria [10 prevalent comorbidities in T2DM. 26 People with T2DM have almost quadruple the risk (hazard ratio [HR] 3.77, P = .001), while those with coronary heart disease are 2.47 (P = .004) times more likely to develop CKD stages 3-5.…”
Section: Burden and Associated Risk Factors For Cardiorenal Complicat...mentioning
confidence: 99%
See 3 more Smart Citations
“…[20][21][22][23] The DISCOVER program illustrated a substantial burden of microvascular complications (including CKD and albuminuria) and macrovascular complications (primarily coronary artery disease, HF, and stroke). 24 Another multinational study (CAPTURE) showed that people with T2DM and established CVD (33%) have a higher burden of renal dysfunction (microalbuminuria [31.8% vs 20.6%], macroalbuminuria [10 prevalent comorbidities in T2DM. 26 People with T2DM have almost quadruple the risk (hazard ratio [HR] 3.77, P = .001), while those with coronary heart disease are 2.47 (P = .004) times more likely to develop CKD stages 3-5.…”
Section: Burden and Associated Risk Factors For Cardiorenal Complicat...mentioning
confidence: 99%
“…Screening programs for early detection of T2DM, compounded by timely utilization of safe and effective therapies, may help prevent complications, thus reducing morbidity and mortality. 6,10 The prevalence of cardiorenal complications in patients with T2DM is rising in the MENA and AFR regions. The cross-sectional Turkish Diabetes Epidemiology (TURDEP)-II survey involving 26 499 adults (≥20 years) showed an alarming rise in the prevalence of T2DM and associated cardiometabolic risk factors, highlighting an urgent need to address this major public health burden.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations